Pump irrigation systems for peach crops in the municipality of Sotaquira department of Boyacá (Revista Cientifica Ingenio Magno, 2020)
The present study was developed in order to identify the current technological state of peach crop irrigation systems in the municipality of Sotaquirá, Boyacá department, which allows defining the main potentializing and limiting aspects for the implementation of transport and pumping systems for irrigation powered by photovoltaic solar energy. For this purpose, a survey tool was applied with a sample of 30 producers that generate a 95% representativeness and a margin of error of 5% over the total producers in the municipality. The validation of the instrument was carried out through an expert panel and pilot survey. The results obtained allowed to define that 30% of producers have an irrigation system, as a critical situation it was identified that no productive system has automated irrigation and the main type of irrigation is the one called by hose. All the producers that have an irrigation system use conventional sources of energy in the pumping process, 60% use gasoline and 40% DIESEL. According to the figures identified, the technological lag in pumping systems is corroborated, especially in the use of alternative nergy sources.
Keywords: Energy for agriculture; alternative energy; solar energy; fruit trees